Effect Variations of Fish Food on Growth in Catfish. (Clarias Garipinus) - Nugraha, Lingga; Kurniawan, Nia (Biotropika: Journal of Tropical Biology, 2013)
ABSTRAK This study was carried out faculty Mathematics UB Malang 1 June 2012. This study aims to determine the effect of variations of food to African catfish (Clarias Gariepinus) using pests (Gold snails) and poultry waste (feces gemak) on the growth of channel catfish as well as to reduce the cost of purchasing an expensive artificial feed, so need to note the retention and protein efficiency ratio of fish needs every day. The variables were observed in this study was the weight, length, body color. The study was conducted using completely randomized design (CRD) with three treatment that feeding by comparing the artificial fish feed plant, fish feed made ââwith gold snails and artificial feed with poultry manure with each ratio 100:0, 70:30, 70:30 @ weight of each fish and each made âârepeated 4 times, with other factors such as pH equated, light intensity, water temperature, water quality, oxygen levels. The results showed that there was no significant difference between the treatment given to the growth of the weight and length of the fish, but mixed with dung feeding quail in the ratio of 70: 30 more profitable because the costs were less. Feeding pellets mixed with the ratio of 70:30 keongmas also beneficial although slightly larger than quail dirt. Although the number of calories produced is less than the controls, but not significantly different, and the provision of a varied diet had no effect on the shape and color of the fish where the fish are shown color remains black and shiny, which means normal. So dirt and keongmas quail can be a safe alternative to feed and to reduce maintenance costs. Â Keywords: Lele Dumbo, food, growth, color Â